Building and coding (physical - skill) for advanced players with handball - Dr. Qahtan Fadhil Mohammed (الرياضة المعاصرة)
It has become obligatory for experts and scientists to strive to develop a number of scientific tests to measure the ability of individuals to perform both physical and skill activity, and many of them have succeeded in building and codifying a large number of testing tools, which have proven to be valid for the purpose for which they were developed, and today the need is very urgent in Designing and coding compound tests to the handball game because of its rapid and noticeable development, and since the handball game relies heavily on shooting skill, through which the team achieves victory over the opposing team, and since the players need strength and high speed in the shooting skill, therefore I must Brother's family Saas provides tests that simulate the requirements to perform this skill, and the importance of research lies in providing a tool for physical and skill testing for some types of strength for handball shooting skill, and through the researcher's follow-up to the game and his knowledge of many scientific sources and references such as research and similar studies did not find a study in this field, and the fact that the tests Available to measure correction skill did not achieve the full objectivity in its results since most of it depends on accuracy only without calculating physical capabilities (speed and strength) despite its importance in performing correction skill, so the researcher must conduct this research in order to provide a means of measuring the correction skill, The aim of the research is to build (physical - skill) tests for some types of power for accurate aiming for advanced players in handball, and to find degrees and standard levels for some types of strength for accuracy of aiming skill for advanced players in handball, the researcher used the descriptive method in the survey method, and the search community represented players of teams participating in The Premier League Handball Championship 2019/2020, whose number is (200) players. The research sample represented (164) players, or 82% of the research community. Composite tests were built according to the scientific foundations of building tests. The SPSS statistical program was used to statistically process the data, and they concludedResearcher to build vehicle tests for some types of precision skill shooting hand reel four tests of their number, and the researcher recommends the use of the final composite tests reached